Arabic language larners' font preferences - Zainuddin, Nurkhamimi; Mat Daud, Nuraihan (IIUM Press, 2012)
The aim of this study is to analyse font type, font size and line length preferred by Arabic language learners when reading on-screen. Studies done on other languages, especially those using Roman scripts, have shown that font size and type affect ease of reading. In this study, Arabic language learners were asked to identify e-books that were easy to read. Majority of them found 14-point font size Simplified Arabic easy to read. However, Arial Unicode was more attractive than the other fonts. Results also indicated that most of them preferred to read texts on full-screen line length.